Ambipolar Nonvolatile Memory Behavior and Reversible Type‐Conversion in MoSe2/MoSe2 Transistors with Modified Stack Interface. (9th October 2022) - Kim, Taewook; Kang, Donghee; Lee, Sol; Jeong, Yeonsu; Cho, Hyunmin; Kim, Junho; Bae, Heesun; Yi, Yeonjin; Kim, Kwanpyo; Im, Seongil
Abstract: 2D semiconductor devices have been studied due to their unique potential in architecture and properties. As one of the unique devices approaches, 2D hetero‐stack channel field‐effect transistors (FETs) have recently been reported, but homo‐stack FETs are rare to find. Here, MoSe2 /MoSe2 homo‐stack transistors are rather fabricated for study. Unlike the equivalently‐thick single MoSe2 FET, homo‐stack FETs show n‐type memory behavior that originates from stack interface‐induced traps. Particularly, when their stack interfaces are engineered by surface oxidation of bottom MoSe2, more stable nonvolatile memory behavior turns out. Short‐term ultraviolet ozone (UVO)‐induced oxidation only results in n‐type memory, but 15 min‐long oxidation surprisingly enables both n‐ and p‐type nonvolatile memory behavior due to nm‐thin MoOx embedded between upper and lower MoSe2 . Furthermore, by alternating gate voltage pulse to the 15 min‐long UVO‐treated FETs, channel polarity conversion appears reversible in a small gate voltage (VGS ) sweep range, which means that the channel type of a transistor can be reversibly modulated via stack interface engineering. It is believed that homo‐stack interface engineering must be one of the approaches to maximize the potential of 2D devices. Abstract : MoSe2 /MoSe2 homo‐stack transistors are fabricated for n‐type memory devices whose nonvolatile memory behavior originates from stack interface‐induced traps via surface oxidation of bottom MoSe2, Here, it is found that long‐term oxidation surprisingly enables ambipolar nonvolatile memory behavior due to nm‐thin MoOx embedded between upper and lower MoSe2 . Moreover, alternating V GS pulses reversibly convert the channel polarity of such homo‐stack transistors.